2003
DOI: 10.1001/archinte.163.22.2696
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Natriuretic Peptide System in Cardiorenal Protection

Abstract: Significant progress has been made in the understanding of the neurohormonal factors that contribute to the progression of chronic renal and cardiac failure and the development of target-organ damage in patients with hypertension and diabetes. We herein review some of these advances, including a new therapeutic strategy for potentially enhancing cardiorenal protection in patients with these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 108 publications
1
23
0
Order By: Relevance
“…Renal ischemia-reperfusion injury (8), impaired vasodilatation (9), neurohormonal activation (10), oxidative stress (11), inflammation (12), and atheroembolism (13) promote AKI following cardiac surgery and cardiopulmonary bypass. In contrast, statins limit oxidant production (14), improve endothelial function (15), and reduce inflammation (16).…”
Section: Introductionmentioning
confidence: 99%
“…Renal ischemia-reperfusion injury (8), impaired vasodilatation (9), neurohormonal activation (10), oxidative stress (11), inflammation (12), and atheroembolism (13) promote AKI following cardiac surgery and cardiopulmonary bypass. In contrast, statins limit oxidant production (14), improve endothelial function (15), and reduce inflammation (16).…”
Section: Introductionmentioning
confidence: 99%
“…Functions of the NPS include the counter-regulation of RAS, and it is suggested that its activation provides organ protection in cardiorenal disease, especially in diabetic patients [43]. …”
Section: Resultsmentioning
confidence: 99%
“…The natriuretic peptide system consists of the ANP, the brain natriuretic peptide, and the C-type natriuretic peptide, each encoded by a separate gene [32]. They are synthesized predominantly in the heart, brain, and kidneys and act via specific receptors (NPr-A, NPr-B, and NPr-C) [14,32].…”
Section: Alterations In the Natriuretic Peptide Systemmentioning
confidence: 99%
“…They are synthesized predominantly in the heart, brain, and kidneys and act via specific receptors (NPr-A, NPr-B, and NPr-C) [14,32]. The natriuretic peptides have a protective role on the development of HTN due to their natriuretic and vasodilatory effects as well as their inhibitory effect on the SNS and the RAAS [14,32].…”
Section: Alterations In the Natriuretic Peptide Systemmentioning
confidence: 99%
See 1 more Smart Citation